2019
DOI: 10.1016/j.ipl.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

New lower bound on the Shannon capacity of C7 from circular graphs

Abstract: We give an independent set of size 367 in the fifth strong product power of C 7 , where C 7 is the cycle on 7 vertices. This leads to an improved lower bound on the Shannon capacity of C 7 : Θ(C 7 ) ≥ 367 1/5 > 3.2578. The independent set is found by computer, using the fact that the set {t · (1, 7, 7 2 , 7 3 , 7 4 ) | t ∈ Z 382 } ⊆ Z 5 382 is independent in the fifth strong product power of the circular graph C 108,382 . Here the circular graph C k,n is the graph with vertex set Z n , the cyclic group of orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…1: The zero-error capacity of the graph C 7 , corresponding to the noisy-typewriter channel with 7 letters, is unknown. Some recent lower and upper bounds are stated in [26].…”
Section: B Tools and Bounds For Zero-error Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…1: The zero-error capacity of the graph C 7 , corresponding to the noisy-typewriter channel with 7 letters, is unknown. Some recent lower and upper bounds are stated in [26].…”
Section: B Tools and Bounds For Zero-error Capacitymentioning
confidence: 99%
“…1. Its zero-error capacity is still unknown, despite several attempts to build zero-error codes on these channels, see [31], [32], and [26]. In Fig.…”
Section: About Cyclesmentioning
confidence: 99%
“…A breakthrough in this field was given by Lovász [12] who proved that Θ(G) = √ 5. Despite many results on Shannon capacity of cycles with 7 vertices C 7 [14,15,17], the capacity problem for C 7 is still open. For disjoint union of two graphs, Alon [2] showed that there exist graphs G and H such that Θ(G + H) > Θ(G) + Θ(H), which disproved a conjectured given by Shannon [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Polak and Schrijver (2019) and Mathew and Östergård (2017) made some progress in research on channels represented by strong powers of cycles. Moreover, Boche and Deppe (2020) proved that the zero-error capacity is uncomputable in the Banach-Mazur and Borel-Turing senses.…”
Section: Introductionmentioning
confidence: 99%